Full text of the SUSURGALUR journal, September 2013 - SUSURGALUR, Editor Journal (SUSURGALUR, 2013)
This journal, with ISSN 2302-5808, was firstly published on March 24, 2013. Since issue of September 2013, the SUSURGALUR-JKSPS journal has been joining publication between ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung with APB UBD (the Academy of Bruneian Studies, University of Brunei Darussalam) and History Program FASS (Faculty of Arts and Social Sciences) UBD in Bandar Seri Begawan, Negara Brunei Darussalam. This journal is published twice a year i.e. every March and September.Â